Deteksi Audit Kepatuhan Sistem Informasi Akuntansi Persediaan Pada Toko Ritel Melalui Pengendalian Internal - Mohammad Ramadhan Priatmojo; Rafa Syahrul Amrulloh; Tri Ratnawati (Manajemen Kreatif Jurnal, 2023)
This study aims to analyze the detection of compliance audits of inventory accounting information systems at retail stores through internal control. An inventory accounting information system is a critical element of retail store operations, and adherence to proper procedures is critical to maintaining the integrity and reliability of inventory data. The research method used is a literature study and descriptive analysis. Data was collected through a literature review related to compliance audit detection. This research also includes a case study to illustrate the application of internal control in the detection of compliance audits in inventory accounting information systems. By implementing proper internal controls, retail stores can minimize the risk of fraud, errors, and losses associated with inventory. This research also shows the need for increased awareness and understanding regarding audit compliance detection among auditors and accounting professionals involved in the retail industry.